THE ANALYSIS OF INTER-INFLUENCE AMONG GLOBAL ISLAMIC INDEX, REGIONAL ISLAMIC INDEX, MACROECONOMICS VARIABLES AND INDONESIA ISLAMIC INDEX (Case study of jakarta islamic indexs (JII), Period 2010-2014 - Susilo Nur Aji Cokro Darsono (EKPI 15 UMY 024, 2015)
*24 The purpose of this study is to examine the relationship among Global Islamic index. Regional Islamic Index, Macroeconomic Variabels and Indonesia Islamic Index. The global Islamic Index is Dow Jones Islamic Market Index.